An Innate Immunity Pathway in the Moss Physcomitrella patens . Issue 6 (7th June 2016) - Bressendorff, Simon; Azevedo, Raquel; Kenchappa, Chandra Shekar; Ponce de León, Inés; Olsen, Jakob V.; Rasmussen, Magnus Wohlfahrt; Erbs, Gitte; Newman, Mari-Anne; Petersen, Morten; Mundy, John
Abstract : A P. patens signaling pathway required for immunity triggered by PAMPs induces growth inhibition, a novel fluorescence burst, cell wall depositions, and accumulation of defense-related transcripts. Abstract: MAP kinase (MPK) cascades in Arabidopsis thaliana and other vascular plants are activated by developmental cues, abiotic stress, and pathogen infection. Much less is known of MPK functions in nonvascular land plants such as the moss Physcomitrella patens . Here, we provide evidence for a signaling pathway in P. patens required for immunity triggered by pathogen associated molecular patterns (PAMPs). This pathway induces rapid growth inhibition, a novel fluorescence burst, cell wall depositions, and accumulation of defense-related transcripts. Two P. patens MPKs (MPK4a and MPK4b) are phosphorylated and activated in response to PAMPs. This activation in response to the fungal PAMP chitin requires a chitin receptor and one or more MAP kinase kinase kinases and MAP kinase kinases. Knockout lines of MPK4a appear wild type but have increased susceptibility to the pathogenic fungi Botrytis cinerea and Alternaria brassisicola . Both PAMPs and osmotic stress activate some of the same MPKs in Arabidopsis. In contrast, abscisic acid treatment or osmotic stress of P. patens does not activate MPK4a or any other MPK, but activates at least one SnRK2 kinase. Signaling via MPK4a may therefore be specific to immunity, and the moss relies on other pathways to respond to osmotic stress.